Synthetic molecules: helping to unravel plant signal transduction - Xuan, Wei (Springer-Verlag, 2013)
The application of small molecules has played a crucial role in identifying novel components involved in plant signalling. Compared to classic genetic approaches, small molecule screens offer notable advantages in dissecting plant biological processes, such as technical simplicity, low start-up costs, and most importantly, bypassing the problems of lethality and redundancy. To identify small molecules that target a biological process or protein of interest, robust and well-reasoned high-throughput screening approaches are essential. In this review, we present a series of principles and valuable approaches in small molecule screening in the plant model system Arabidopsis thaliana. We also provide an overview of small molecules that led to breakthroughs in uncovering phytohormone signalling pathways, endomembrane signalling cascades, novel growth regulators, and plant defence mechanisms. Meanwhile, the strategies to deciphering the mechanisms of these small molecules on Arabidopsis are highlighted. Moreover, the opportunities and challenges of small molecule applications in translational biology are discussed.